Acute clinical presentation of nonischemic cardiomyopathies: early detection by cardiovascular magnetic resonance. (15th April 2023) - Todiere, Giancarlo; Barison, Andrea; Baritussio, Anna; Cipriani, Alberto; Guaricci, Andrea Igoren; Pica, Silvia; Indolfi, Ciro; Pontone, Gianluca; Dellegrottaglie, Santo
Abstract : Nonischemic cardiomyopathies include a wide range of dilated, hypertrophic and arrhythmogenic heart muscle disorders, not explained by coronary artery disease, hypertension, valvular or congenital heart disease. Advances in medical treatments and the availability of implantable cardioverter defibrillators to prevent sudden cardiac death have allowed a substantial increase in the survival of affected individuals, thus making early diagnosis and tailored treatment mandatory. The characterization of cardiomyopathies has received a great boost from the recent advances in cardiovascular magnetic resonance (CMR) imaging, which, to date, represents the gold standard for noninvasive assessment of cardiac morphology, function and myocardial tissue changes. An acute clinical presentation has been reported in a nonnegligible proportion of patients with nonischemic cardiomyopathies, usually complaining of acute chest pain, worsening dyspnoea or palpitations; 'hot phases' of cardiomyopathies are characterized by a dynamic rise in high-sensitivity troponin, myocardial oedema on CMR, arrhythmic instability, and by an increased long-term risk of adverse remodelling, progression of myocardial fibrosis, heart failure and malignant ventricular arrhythmias. Prompt recognition of 'hot phases' of nonischemic cardiomyopathies is of utmost importance to start an early, individualized treatment in these high-risk patients. On the one hand, CMR represents the gold standard imaging technique to detect early and typical signs of ongoing myocardial remodelling in patients presenting with a 'hot phase' nonischemic cardiomyopathy, including myocardial oedema, perfusion abnormalities and pathological mapping values. On the other hand, CMR allows the differential diagnosis of other acute heart conditions, such as acute coronary syndromes, takotsubo syndrome, myocarditis, pericarditis and sarcoidosis. This review provides a deep overview of standard and novel CMR techniques to detect 'hot phases' of cardiomyopathies, as well as their clinical and prognostic utility.